Management of Ek Kushtha (Psoriasis) with Virechana Karma - A Clinical Case Report (AYUSHDHARA, 2025)
Virechana is a therapeutic purgation in Ayurveda that mainly addresses imbalances of Pitta Dosha in Ek Kushtha, hence aiding in the removal of accumulated endotoxins. This purification process assists in reestablishing Dosha harmony, which is crucial for achieving long-term relief and preventing the recurrence of the condition. The clinical features of Ek Kushtha can be corelated with psoriasis. The three clinical features seen in patient of psoriasis are Auspitz sign, candle grease sign and Koebner’s phenomenon which can be correlated with Aswedanam Mahavastu Matsyashakalopamam. A 48-year-old male patient came to our Panchakarma OPD presenting with erythematous patches across the body. Virechana karma was planned after clinical examination. Abhyantra snehan was given in Arohana matra (30ml) with Panchtikta Ghrit followed by Sarvanga Abhyanga and Sarvanga Swedan. Patient was subjected to Virechana with Trivrit Lehya and Draksha Kashaya. For the next seven days, the patient underwent Sansarjana krama.